PROBLEMATIKA KEPEMIMPINAN PENDIDIKAN DAN SOLUSINYA - Izudin Hasan; Norman Rade Arfiansyah; Irnie Victorynie (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Leadership in education is a crucial factor influencing the quality of education in Indonesia. This study addresses the challenges faced by school principals in improving their leadership capacity, which significantly affects the overall educational ecosystem. Key issues include the lack of managerial skills among principals, inadequate research on educational leadership, and non-merit-based selection processes for school leaders. Furthermore, the rapid technological advancements and globalization present additional challenges for principals in adapting to new educational demands. This research explores these problems and suggests solutions such as reforming principal training programs, enhancing research-based decision-making, implementing merit-based selection processes, and preparing principals for technological and global changes. The findings aim to contribute to the improvement of educational leadership in Indonesia.